Development of novel coatings to resist fireside corrosion in biomass-fired power plants - Orlicka, Dominika (Cranfield University, 2016)
The emission of CO2 to the atmosphere from firing conventional fossil fuels has become a major concern for the power industry, due to the enhanced greenhouse effect and global warming predictions. The increasing worldwide demand for electricity production is another issue. The replacement of fossil fuels with increasing quantities of biomass is of interest as biomass is considered to be carbon neutral and is widely distributed. Unfortunately, due to its composition, the risk of fireside corrosion found on heat exchangers (super- heaters and re-heaters) is greater than in coal-fired plants. Consequently, biomass-fired power plants operate at lower steam temperatures and pressures, leading to their poorer efficiency. Biomass-fired power plants suffer from alkali chloride-induced corrosion, considered faster and more severe than alkali sulphate-based corrosion common in traditional coal-fired plants. The main aim of this project was to develop a range of novel coating compositions which would be resistant to fireside corrosion found on boiler tubes in biomass-fired power plants. To accomplish this, studies were carried out into salt stabilities, coating oxidation and deposit corrosion. Salt stability experiments have resulted in improved understanding of the evaporation and sulphidation behaviour of KCl, NaCl, K2SO4 and Na2SO4 at high temperatures in environments containing HCl and SO2. KCl was chosen as a deposit for coating screening. Two-target magnetron co-sputtering was successfully used to deposit a range of coating compositions. These coatings were analysed at 550°C in corrosion environments containing combinations of HCl, KCl and water vapour. The addition of gaseous HCl did not have a significant influence on the coating degradation compared to similar tests in air. Deposited KCl significantly increased the corrosion rate, whereas adding 10% moisture to the environment with KCl had little additional effect. The growth of either protective Cr2O3 or less protective mixed oxides was observed on the different coating compositions. The best performing coatings had compositions in the range: 26.2 – 79.4 at% Cr, 12.1 – 62.9 at% Fe, 8.5 – 10.9 at% Al.